(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
This research aimed to provide a conceptual framework for black marketing and marketing activities in terms of concept, characteristics, and objectives, and to define marketing audit and the importance of its desired goals when applied in economic units. It also discussed the role of marketing activity audits in reducing detrimental marketing practices. Furthermore, the study analyzed and audited the marketing activity data of the Mesopotamia General Seed Company (case study) to assist in identifying shortcomings in marketing performance. For this purpose, data necessary for analyzing and auditing the marketing activities of the Mesopotamia General Seed Company were collected. The researchers examined the company’s approved procedures for presenting financial statements and conducted direct interviews with officials and employees at the case study company, who strive to improve their products according to standards and specifications that achieve the highest levels of production and quality, enabling competition and market presence. The research concluded several findings, the most important being that black marketing leads to serious economic, social, and political effects, including destabilizing the local economy through price inflation and reducing fair competition, encouraging illegal activities that increase corruption and crime rates, and threatening state entities by using illicit money to influence the political and security systems. Additionally, marketing audit is a comprehensive, systematic, and independent process aimed at evaluating the marketing environment and the performance of the economic unit, with the aim of identifying opportunities and problems and suggesting improvements in strategies and plans to achieve better marketing performance. The study recommended several actions, including improving internal resource management to ensure their effective use, conducting public awareness campaigns about the negative impacts of black marketing on the economy and society to encourage consumers to support only legal products, restructuring seed processing operations to be more effective, reducing routine procedures, and facilitating seed receipt by farmers, with more accessible delivery points for farmers.